Microscopic Dynamic Mechanism of Irreversible Thermodynamic Equilibration of Crystals - Anatoly Yu. Zakharov; Maxim A. Zakharov (Quantum Reports, 2021)
The dynamics of free and forced vibrations of a chain of particles are investigated in a harmonic model taking into account the retardation of interactions between atoms. It is found that the retardation of interactions between particles leads to the non-existence of stationary free vibrations of the crystal lattice. It is shown that in the case of a stable lattice, forced vibrations, regardless of the initial conditions, pass into a stationary regime. A non-statistical dynamic mechanism of the irreversible thermodynamic equilibration is proposed.